2014
DOI: 10.1111/bph.12713
|View full text |Cite
|
Sign up to set email alerts
|

IL‐6 in diabetes and cardiovascular complications

Abstract: IL‐6 is a pleiotropic cytokine that participates in normal functions of the immune system, haematopoiesis, metabolism, as well as in the pathogenesis of metabolic and cardiovascular diseases. Both pro‐ and anti‐inflammatory roles of IL‐6 have been described, which are distinguished by different cascades of signalling transduction, namely classic and trans‐signalling. The present review summarizes the basic principles of IL‐6 signalling and discusses its roles in diabetes and associated cardiovascular complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
122
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(132 citation statements)
references
References 86 publications
(99 reference statements)
7
122
0
3
Order By: Relevance
“…Emphasis should be put on the distinct destinations diverged by these two arms of IL-6 signaling and the value of developing therapeutic strategies to specifically target the deleterious trans-signaling of IL-6 [130]. Blocking IL-6 trans-signaling could prevent inflammation, while activating membrane-bound signaling could promote insulin sensitivity [131].…”
Section: Approaches Targeting Il-6mentioning
confidence: 99%
“…Emphasis should be put on the distinct destinations diverged by these two arms of IL-6 signaling and the value of developing therapeutic strategies to specifically target the deleterious trans-signaling of IL-6 [130]. Blocking IL-6 trans-signaling could prevent inflammation, while activating membrane-bound signaling could promote insulin sensitivity [131].…”
Section: Approaches Targeting Il-6mentioning
confidence: 99%
“…The study also demonstrated that macrophages, which mediated the pathogenesis of nephrotoxic nephritis, accumulated in the kidney, expressed high levels of IL-6R and proliferated in IL-6-deficient mice; treatment with IL-6 strongly Page 16 of 64 A c c e p t e d M a n u s c r i p t 16 inhibited macrophage proliferation [48]. These accumulated results raise a concern suggesting that trans-signaling mediated by the soluble IL-6R and classical signaling mediated by the surface IL-6R may have different effects depending on the systems being studied; the former is thought to be pro-inflammatory and the latter is anti-inflammatory [49]. However, given that gp130 is shared by many different cytokine signaling pathways, it is possible that the difference between classical-and trans-signaling pathways may be accounted in part by blockade of the other cytokines that also signal via gp130 [2].…”
Section: Il-6 and Immune-mediated Renal Diseasesmentioning
confidence: 99%
“…In contrast, IL-6 elicits its effects via binding a membrane-bound IL-6 receptor complexed with the co-receptor gp130 (classic signalling), or by binding a soluble IL-6 receptor (sIL-6Rα) that binds to gp130 ( trans -signalling), stimulating Janus kinase (JAK)-mediated activation of the signal transducer and activator of transcription-3 (STAT3) transcription factor predominantly via phosphorylation of Tyr705 (Salt and Palmer, 2012, Qu et al., 2014). The cytokine-stimulated NFκB, JNK and JAK/STAT pathways culminate in the secretion of multiple pro-inflammatory cytokines and chemokines, including monocyte chemoattractant protein-1 (MCP-1), which stimulates the activation and infiltration of macrophages (Cohen, 2014, Brenner et al., 2015; Salt and Palmer, 2012, Qu et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The cytokine-stimulated NFκB, JNK and JAK/STAT pathways culminate in the secretion of multiple pro-inflammatory cytokines and chemokines, including monocyte chemoattractant protein-1 (MCP-1), which stimulates the activation and infiltration of macrophages (Cohen, 2014, Brenner et al., 2015; Salt and Palmer, 2012, Qu et al., 2014). In adipose tissue, macrophages undergo a shift in polarisation from an anti-inflammatory ‘alternatively activated’ state, to a ‘classically activated’ pro-inflammatory state, which has been reported to dominate in WAT in obesity (Lumeng et al., 2007).…”
Section: Introductionmentioning
confidence: 99%